Water (management) as a decisive factor in the land use planning of agriculture in an urbanising context - Georges Allaert; Hans Leinfelder; Peter Vanden Abeele; David Verhoestraete (European Regional Science Association (ERSA), 2005)
The Centre for Mobility and Physical Planning of the Ghent University coordinates a two-year research project about the preconditions for sustainable land use by agriculture in (the Flemish) urbanising network society. The project questions the traditional legitimacy of agriculture in planning to claim the majority of the surface, merely because of economical reasons. If agriculture wants to have a raison d'être in urbanised and urbanising society, it will have to meet the quality demands of network society which are more than economical demands. The degree in which agriculture is capable in fulfilling these needs, will be decisive for the spatial development perspectives for agriculture. Questioning the traditional legitimacy of agriculture in planning is also questioning the actual planning discourse that has been dominating policy for the last three decades, not only in Belgium but in the most of North-Western Europe. This dominant discourse considers city and countryside as antipoles and is still translated in current planning initiatives that strengthen compact cities and restrict new developments in the countryside. This discourse is no longer tenable within the concept of network society, especially in the densely populated and fragmentarily urbanised Flemish region in Belgium where numerous urban activities and functions are silently and autonomously taking over the countryside. The research tries to evaluate the spatial development perspectives for agriculture of three alternative planning discourses about the spatial relation between city and countryside through design-oriented research. These alternative discourses try to meet the characteristics of network society in a different way than the dominant discourse: the first one considers city and countryside as networks of activities, the second one sees them as systems of places with an identity and the last one defines the ecosystem as the common layer of city and countryside. As the design-oriented research is evolving in a study area around Kortrijk and Roeselare in the Western part of Flanders, it becomes clear that each of these three alternative discourses is confronted with water (management) as a decisive factor in the planning of the land use of agriculture in relation to urban activities in the countryside. This is of course obvious for the ecosystem discourse as water is one of the driving forces in the ecosystem. But also in the network of activities discourse the exhaustion of the ground water supply seems to be one of the main frustrations, to be solved through planning, between the international network of activities of the farming industry and the local/regional network of villages and agriculture. Finally, water seems to be an important factor in defining and planning the identity of places in the system of places discourse. The paper will primarily focus on the theoretical background of dominant and alternative planning discourses about city and countryside. Consequently it will summarise the results of the water related design-oriented planning research on and the spatial development perspectives for agriculture of the three alternative planning discourses in the study area.
Keywords: 330